Validation of the multimedia version of the RDC/TMD axis II questionnaire in Portuguese - Ricardo Figueiredo Cavalcanti; Luciana Moraes Studart; Maurício Kosminsky; Paulo Sávio Angeiras de Goes (University of São Paulo, 2010)
OBJECTIVE: The aim of the study was to validate the multimedia version of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) Axis II Questionnaire in Portuguese language. MATERIAL AND METHODS: The sample comprised 30 patients with signs and symptoms of temporomandibular disorders (TMD), evaluated at the Orofacial Pain Control Center of the Dental School of the University of Pernambuco, Brazil, between April and June 2006. Data collection was performed using the following instruments: Simplifed Anamnestic Index (SAI) and RDC/TMD Axis II written version and multimedia version. The validation process consisted of analyzing the internal consistency of the scales. Concurrent and convergent validity were evaluated by the Spearman's rank correlation. In addition, test and analysis of reproducibility by the Kappa weighted statistical test and Spearman's rank correlation test were performed. RESULTS: The multimedia version of the RDC/TMD Axis II questionnaire in Portuguese was considered consistent (Crombrach alpha = 0.94), reproducible (Spearman 0.670 to 0.913, p<0.01) and valid (p<0.01). CONCLUSION: The questionnaire showed valid and reproducible results, and represents an instrument of practical application in epidemiological studies of TMD in the Brazilian population.